2020
DOI: 10.3389/fpsyt.2020.00079
|View full text |Cite
|
Sign up to set email alerts
|

Adult Mild Encephalitis With Reversible Splenial Lesion Associated With Delirious Mania: A Case Report

Abstract: Mild encephalitis with reversible splenial lesion is a rare clinic-radiological entity presenting with neurological and neuropsychiatric symptoms associated with cerebral lesion/s. Delirious mania is a severe psychiatric syndrome characterized by acute onset of delirium, excitement, and psychosis with a high mortality rate. In this paper, we present a case report of mild encephalitis with reversible splenial lesion clinically presenting as delirious mania and evolving into life-threatening multi-organ failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In general, it would seem that patients with ASDs show a trend towards lower levels of both DHA and AA in comparison with healthy controls [ 46 , 48 , 54 , 57 , 59 , 60 , 61 , 63 , 65 ], as well as an elevated ω6/ω3 ratio [ 39 , 54 , 58 , 60 ]. Again, these alterations support the hypothesis of an inflammatory dysregulation in patients affected by psychiatric conditions [ 80 , 81 , 82 ] including ASDs [ 83 ]. In addition, it was demonstrated that changes in lipid profile may enhance systemic and brain oxidative stress affecting synaptic function [ 75 , 84 ], paving the way for new therapeutic perspectives [ 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…In general, it would seem that patients with ASDs show a trend towards lower levels of both DHA and AA in comparison with healthy controls [ 46 , 48 , 54 , 57 , 59 , 60 , 61 , 63 , 65 ], as well as an elevated ω6/ω3 ratio [ 39 , 54 , 58 , 60 ]. Again, these alterations support the hypothesis of an inflammatory dysregulation in patients affected by psychiatric conditions [ 80 , 81 , 82 ] including ASDs [ 83 ]. In addition, it was demonstrated that changes in lipid profile may enhance systemic and brain oxidative stress affecting synaptic function [ 75 , 84 ], paving the way for new therapeutic perspectives [ 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, encephalitis should always be considered in the differential diagnosis of delirious mania. 4 , 8 There is a high incidence of catatonic findings in delirious mania, and the term delirious catatonia has been suggested as more illustrative of the actual clinical syndrome. 1 , 2 , 8 Both catatonia and delirious mania may worsen to NMS after the administration of first-generation antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Studies have also mentioned the role of neuroinflammation and acute insults to the corpus callosum as possible precipitants. 4 , 9 …”
mentioning
confidence: 99%
“…A large-scale heritability study of BR (Miller et al, 2010) demonstrated the following: (c) monozygotic versus dizygotic twin correlations for BR rate were significant but this was not so for other BR measures; (d) genetic modeling analyses indicated a substantial genetic contribution to individual variation in BR rate; (e) wide individual variation and very high within-session reliability of BR rate; and (f) high between-session (retest) reliability of BR rate. lesion-can present with mania when the callosal lesion is present, that settles when the lesion disappears (Bellani et al, 2020). The relationship between altered callosal anatomy and unihemispheric sleep in several species has also been detailed (Dell et al, 2016;Lyamin et al, 2008;Manger & Siegel, 2020).…”
Section: Further Testing the Sticky Switch Modelmentioning
confidence: 99%
“…Here I would distinguish callosal abnormalities in BD causing a slow IHS (which Pettigrew and I doubted, focusing instead on a slowed subcortical or brainstem bistable oscillator) from such abnormalities being the consequence of a slow IHS (or indeed of repeated periods of being “stuck” in the left‐ or right‐activated state). It is interesting to note that callosal agenesis is known to be associated with slow rates of perceptual rivalry (Fagard et al, 2008), and reversible callosal lesions—such as those associated with the clinical condition, mild encephalitis with reversible splenial lesion—can present with mania when the callosal lesion is present, that settles when the lesion disappears (Bellani et al, 2020). The relationship between altered callosal anatomy and unihemispheric sleep in several species has also been detailed (Dell et al, 2016; Lyamin et al, 2008; Manger & Siegel, 2020).…”
Section: Slow Br In Bd and The Sticky Switch Model Of Bdmentioning
confidence: 99%